Optimizing DSA parameters for enhanced radiation safety in interventional surgery - Zeng, XunJin; Wang, Hao; Chen, Guang (Frontiers in Public Health, 2025)
ObjectiveThe study aims to establish a reliable method for reducing radiation dose by analyzing variations in radiation dose from digital subtraction machines (DSA).MethodsThe study investigates changes in bed plate height (80–110 cm), detection height (0–30 cm), visual field size (6 × 6 inches and 12 × 12 inches), and radiation doses affecting various body parts, including the lens, thyroid, chest, gonads, and lower limbs. Radiation doses were measured using Raysafe X2 dosimetry for patients and AT1123 meter for operators.ResultsCompared to ordinary fluoroscopy, the low-dose fluoroscopy mode reduced the patient's radiation dose by 50.8% (from 13.2 to 6.5 mGy/min) and the operator's scattered radiation dose by 25–34% (lens dose reduced from 0.72 to 0.47 mGy). In photographic mode, the radiation dose was 3–4 times higher than in ordinary fluoroscopy (e.g., 53.9 vs. 13.2 mGy/min). Raising the bed plate height from 80 to 110 cm reduced the patient's direct radiation dose by 45.5% (from 24.2 to 13.2 mGy/min). The correct application of protective devices reduced the operator's scattering radiation by more than 10 times (e.g., gonads dose reduced from 4.07 to 0.41 mGy).ConclusionSelecting the appropriate bed plate (90–100 cm) and detector height (10–20 cm), along with an optimal visual field (6 × 6 inches), can effectively reduce radiation doses for both patients and operators. The proper use of protective devices in peripheral interventional surgery is crucial for reducing scatter radiation, with reductions exceeding 90% in some cases.